Loss of ULK1 Attenuates Cholesterogenic Gene Expression in Mammalian Hepatic Cells - Rajak, Sangam; Iannucci, Liliana F.; Zhou, Jin; Anjum, B.; George, Nelson; Singh, Brijesh K.; Ghosh, Sujoy; Yen, Paul M.; Sinha, Rohit A. (Frontiers in Cell and Developmental Biology, 2020)
The hepatic mevalonate (MVA) pathway, responsible for cholesterol biosynthesis, is a therapeutically important metabolic pathway in clinical medicine. Using an unbiased transcriptomics approach, we uncover a novel role of Unc-51 like autophagy activating kinase 1 (ULK1) in regulating the expression of the hepatic de novo cholesterol biosynthesis/MVA pathway genes. Genetic silencing of ULK1 in non-starved mouse (AML-12) and human (HepG2) hepatic cells as well as in mouse liver followed by transcriptome and pathway analysis revealed that the loss of ULK1 expression led to significant down-regulation of genes involved in the MVA/cholesterol biosynthesis pathway. At a mechanistic level, loss of ULK1 led to decreased expression of SREBF2/SREBP2 (sterol regulatory element binding factor 2) via its effects on AKT-FOXO3a signaling and repression of SREBF2 target genes in the MVA pathway. Our findings, therefore, discover ULK1 as a novel regulator of cholesterol biosynthesis and a possible druggable target for controlling cholesterol-associated pathologies.